Modelo hierárquico log-logístico : uma aplicação no estudo da Linezolida - Braguim, Simone Demeis (2015)
This paper proposes Log-Logistic Modelapplication in the study that checks the survival time of patients after the use of the antibiotic linezolid, as well as the effects that are caused by this drug. The Log-Logistic Model was an alternative to theWeibull model, which is widely used in survival analysis. In this context, Bayesian inference techniques were employed to estimate the parameters. The data that were obtained from patients treated over the period of 2008 to 2010 at Hospital Universitário de Maringá (HUM), with variable reactions the length of stay of patients in the intensive care unit (ICT). In order to estimate the parameter, it was generated three chains using for so, MCMC methods. In addition, it was considered some charts and tests to analyze the adjustment and convergence of these chains